2004
DOI: 10.1021/la036142z
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Effects on the Reaction between an Arenediazonium Salt and 6-O-Octanoyl-l-ascorbic Acid. Kinetics and Mechanism of the Reaction

Abstract: The effects of 6-O-octanoyl-L-ascorbic acid, VC8, on the reaction with 3-methylbenzenediazonium, 3MBD, tetrafluoroborate were investigated in the absence and in the presence of sodium dodecyl sulfate, SDS, cetyltrimethylammonium bromide, CTAB, and tetradecyltrimethylammonium bromide, TTAB, micelles at different pHs by employing a combination of UV-vis spectroscopy, high-performance liquid chromatography, HPLC, and differential pulse polarography techniques. VC8 behaves as a typical surfactant in aqueous soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…Proposed reaction mechanism for solvolysis of ArN 2 ϩ in EtOH/H 2 O mixtures; the reactive EtOH molecule is one of those in the solvation shell of the ArN 2 ϩ ions; k w and k c stand for the thermal rate constant and for the first-order rate constant for the decomposition of the ArN 2 OEt complex, respectively, and K stands for the equilibrium constant for complex formation number of ascorbate ions, for which the formation of such an intermediate was detected experimentally by employment of electrochemical methods. [9,20] The assumption of a rate-limiting decomposition of the diazo ether is also consistent with reported results for other O-coupling reactions [1,3,33,34] and was experimentally examined in reactions of arenediazonium ions where geometric restrictions apply. [21,35] From Scheme 2, Equation (1) can be derived, where k w and k c are the rate constants for the spontaneous thermal decomposition of ArN 2 ϩ and the rate constant for decomposition of the complex, respectively, and…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Proposed reaction mechanism for solvolysis of ArN 2 ϩ in EtOH/H 2 O mixtures; the reactive EtOH molecule is one of those in the solvation shell of the ArN 2 ϩ ions; k w and k c stand for the thermal rate constant and for the first-order rate constant for the decomposition of the ArN 2 OEt complex, respectively, and K stands for the equilibrium constant for complex formation number of ascorbate ions, for which the formation of such an intermediate was detected experimentally by employment of electrochemical methods. [9,20] The assumption of a rate-limiting decomposition of the diazo ether is also consistent with reported results for other O-coupling reactions [1,3,33,34] and was experimentally examined in reactions of arenediazonium ions where geometric restrictions apply. [21,35] From Scheme 2, Equation (1) can be derived, where k w and k c are the rate constants for the spontaneous thermal decomposition of ArN 2 ϩ and the rate constant for decomposition of the complex, respectively, and…”
Section: Resultssupporting
confidence: 80%
“…In the alternative inner-sphere mechanism, reduction of the arenediazonium ion is preceded by the formation of a complex, namely ArϪNϭNϪOϪR, which was detected experimentally in some dediazoniations. [9,20,21] S-shaped curves such as those shown in Figures 1, 2, and 3 (A) are usually observed in reactions of acid-base pairs in which both forms are attainable and show different reactivities. [31] Under our experimental conditions, only two specimens may undergo acid-base processes: the ArN 2 ϩ ions and EtOH.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…First, to expand our current knowledge on the reactions of arenediazonium ions with polyhydroxylated antioxidants as they have been very much less investigated than those with the mono-and dihydroxylated phenol derivatives [1] [4]. Previous dediazoniation work with antioxidants such as ascorbic acid or methyl gallate, which do not possess structures able to build up very high electron densities at one or more C-atoms, showed that the reactions do not proceed through the C-coupling pathway but via the formation of transient diazo ethers [17] [18] [23] [24].…”
mentioning
confidence: 99%